The First Report of Rhino DNA in Thailand: A Possible Extinct Indian Javan Subspecies, Rhinoceros sondaicus inermis - Yada Katanyuphan; Pipad Krajaejun; Athiwat Wattanapituksakul; Wunrada Surat (Animals)
The Javan rhino is a critically endangered species that has become extinct in several Asian countries, including Thailand. There are three Javan rhino subspecies: Rhinoceros sondaicus sondaicus, R. s. annamiticus, and R. s. inermis, and the first two subspecies existed in Thailand decades ago. However, no genetic study on Thai rhinos has been reported. In this study, we amplified a partial D-loop region of two ancient rhino specimens dated to approximately 100 years before present, from southwest Thailand. Then, we constructed phylogenetic trees and a haplotype network based on the D-loop sequences of the Thai rhinos and 39 Javan, Sumatran, and Indian rhinos from the GenBank database. The ancient Thai rhino DNA belonged to Javan rhinos and was clearly separated from R. s. annamiticus and R. s. sondaicus. The nucleotide differences among the ancient Thai, R. s. annamiticus, and R. s. sondaicus rhino DNA were 5.14–8.30%, similar to those between two white rhino subspecies. Moreover, species delimitation analyses confirmed that the ancient Thai rhinos should belong to another Javan rhino subspecies, possibly the extinct Indian Javan rhino. This is the first report of rhino DNA from Thailand and possibly the Indian Javan rhino DNA, which could be used for evolutionary studies.